Credit Risk and Microfinance Performance in Pakistan: The Moderating Role of Board Risk Committee - Khalid, Hafeez; Salawati, Sahari; Burhan, Ahmed (Human Resource Management Academic Research Society, 2025)
This study investigates the influence of credit risk on the financial performance of microfinance institutions (MFIs) in Pakistan, with a particular focus on the moderating role of the Board Risk Committee Index (RCINDEX). Using panel data from 19 microfinance banks spanning the years 2012 to 2021, the study applies fixed-effects regression with robust standard errors to assess the relationships among key variables. Credit risk is proxied by Portfolio at Risk (PAR) and Non-Performing Loans (NPL), while financial performance is measured using Return on Assets (ROA), Return on Equity (ROE), and Operational SelfSufficiency (OSS). The RCINDEX is constructed as a standardized composite of risk committee size, independence, and competence. The findings reveal that both PAR and NPL are significantly negatively associated with MFI performance, indicating that increased credit risk compromises profitability and sustainability. However, the RCINDEX exhibits a significant positive moderating effect, suggesting that well-structured risk committees can mitigate the adverse consequences of credit risk. These results align with agency and stakeholder theories, which highlight the critical role of governance mechanisms in managing risk and enhancing institutional performance. The study offers practical implications for MFI regulators, boards of directors, and policymakers seeking to strengthen governance frameworks and ensure financial sustainability in emerging economies.